2023
DOI: 10.1371/journal.pone.0285473
|View full text |Cite
|
Sign up to set email alerts
|

Cellular apoptosis and cell cycle arrest as potential therapeutic targets for eugenol derivatives in Candida auris

Abstract: Candida auris, the youngest Candida species, is known to cause candidiasis and candidemia in humans and has been related to several hospital outbreaks. Moreover, Candida auris infections are largely resistant to the antifungal drugs currently in clinical use, necessitating the development of novel medications and approaches to treat such infections. Following up on our previous studies that demonstrated eugenol tosylate congeners (ETCs) to have antifungal activity, several ETCs (C1-C6) were synthesized to find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Eugenol-based hybrid molecules 32 in Figure 5 showed notable antifungal activity against C. auris , resulting from its capability to induce apoptosis and cell cycle arrest. This compound’s low toxicity towards red blood cells compared to eugenol reveals its safe usage in vivo [ 106 ]. P’eret et al demonstrated the antifungal activity of novel imidazoles and 1,2,4-triazoles hybrid molecules synthesized from dihydroeugenol and eugenol.…”
Section: Natural Productsmentioning
confidence: 99%
“…Eugenol-based hybrid molecules 32 in Figure 5 showed notable antifungal activity against C. auris , resulting from its capability to induce apoptosis and cell cycle arrest. This compound’s low toxicity towards red blood cells compared to eugenol reveals its safe usage in vivo [ 106 ]. P’eret et al demonstrated the antifungal activity of novel imidazoles and 1,2,4-triazoles hybrid molecules synthesized from dihydroeugenol and eugenol.…”
Section: Natural Productsmentioning
confidence: 99%
“…13 Since molecular modification of the structures of bioactive natural molecules is a widely used approach to obtain drug candidates with improved efficacy and reduced toxicity, eugenol has been used as a target molecule for the preparation of novel semi-synthetic bioactive compounds. [14][15][16][17][18] Recently, some of us have reported the synthesis and biological activity of a series of racemic mixtures of eugenol derivatives obtained by structural modifications of eugenol at the allyl group. 19 In particular, compound 1, whose structure is shown in Figure 1, showed in vitro antimicrobial activity.…”
Section: Introductionmentioning
confidence: 99%
“…Since molecular modification of the structures of bioactive natural molecules is a widely used approach to obtain drug candidates with improved efficacy and reduced toxicity, eugenol has been used as a target molecule for the preparation of novel semi‐synthetic bioactive compounds 14–18 …”
Section: Introductionmentioning
confidence: 99%
“…18,19 Furthermore, click chemistry techniques, such as the CuAAC reaction, facilitate the synthesis of these hybrid molecules with improved efficiency and precision. 20 By harnessing the synergistic properties of triazoles and quinolines, and in continuation of our search for better antifungal leads, [21][22][23][24] in this study, we synthesized new triazole bridged quinoline derivatives and evaluated them for their antifungal activity prole. Furthermore, we investigated their mechanisms of action and predicted their physicochemical properties to pinpoint lead antifungal molecules with drug-like properties.…”
Section: Introductionmentioning
confidence: 99%